A lógica empresarial no ensino superior brasileiro: implicações para alunos e professores - Leite, Claudia da Silva (2015)
The purpose of this research was to analyze the most valued characteristics of university professor in the perception of students from two private institutions. The theme was observed in historical perspective, as from University Reform in 1968, and taking as fundamental reference three periods (1970, 1990 and today) as also three authors Martins (1988, 1993, 2000, 2005 and 2009), Grigoli (1990), and Freitas (2004 a, 2004b and 2012); a question was applied to the students of graduation course in Business Administration and two technology courses (Logistics and Human Resources).The 588 characteristics obtained from 164 undergraduate students and 105 students of technological courses were analyzed as a whole, allowing grouping them into three categories: knowledge, didacticism, and interpersonal relationship; thereafter, two additional analysis were performed: for each collaborator, individually, and a comparison between courses and periods. According to the results, firstly the professor s didacticism stands out and the interpersonal relationship comes secondly, as an exception only for the undergraduate students of the morning period, for whom, in individual analysis, the knowledge is the second option. The comparison of these three moments in the history of higher education in the country illustrates that the business logic increased, to expand the supply of jobs for the middle layers of population in the 1970´s and for the low income classes twenty years later. It also shows that this expansion led to the public education this business logic, which started with the university reform inherited from the 1964 civil-militar government